Thermodynamic and kinetic aspects of AlN crystal formation on (0001)Al2O3 surface by ammonia MBE. Issue 3 (27th February 2014) - Malin, Timur; Mansurov, Vladimir; Galitsyn, Yury; Zhuravlev, Konstantin
Abstract: Influence of temperature on AlN formation on (0001) Al2 O3 surface under ammonia flux (nitridation process) has been investigated by high‐energy electron diffraction. A significant temperature dependence of AlN formation rate in the temperature range of 850‐940 °C has been found whereas the formation rate is almost constant at temperatures higher than 940 °C. A kinetic scheme of the surface reactions is developed. The values of kinetic constants for the scheme at the low temperature range are found: k1 P=6×10 4 exp(‐1.5eV/kT), k2 =7×10 19 exp (‐5.3eV/kT), k3 =3×10 13 exp(‐4eV/kT). For the high temperature range the AlN formation process is described as a surface phase transition in AlN lattice gas. Parameters of lateral interaction between filled AlN cells are determined and the critical temperature of the phase transition is found (Tc =795 °C). (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)